Beauty and the Beast: Tracing Patriarchal Panopticism in Louise O’Neill’s Only Ever Yours - P. Shubha; S. Christina Rebecca (The Grove - Working Papers on English Studies, 2024)
Only Ever Yours is a dystopian narrative underlining a feminist discourse that critiques the impractical obsessions of the masculine culture over the beauty standards of women. Set in an intensely regimented institutional structure in which young girls are tamed by an androcentric authority, the novel magnifies the gravity of patriarchal practices in reducing the status of women into mere objects by overemphasising their physical appearance and sensuality. This paper interrogates the living condition of the female characters that are subject to rigorous control mechanisms of the institution that seeks to mould them into ideal companions for young men adhering to patriarchal stereotypes. Drawing on Michel Foucault’s concept of ‘Panopticism’, this paper critically examines the representation of control structure in the select text, revealing its profound entrenchment of patriarchal ideologies. Moreover, it highlights the reciprocity between the panoptic system and the patriarchal gaze in enforcing a self-disciplinary inclination in women and examines its psychological repercussions on them.